Survey on New Zealanders' attitudes towards and knowledge of macroeconomic policy issues: Documentation of survey methodology and descriptive results - Bernd Hayo; Florian Neumeier (Philipps-University Marburg, School of Business and Economics, 2016)
This paper provides background information and basic descriptive statistics for a representative survey of the New Zealand population conducted on our behalf by Research New Zealand in May 2016. The survey addresses important fiscal and monetary policy issues, including: (1) public preferences for public debt and fiscal consolidation; (2) awareness of the government's Fiscal Strategy Report; (3) citizens' monitoring of and reaction to inflation and their inflation expectation formation; (4) knowledge and support for the Policy Target Agreement between the Reserve Bank of New Zealand and the government; (5) trust in economic institutions; and (6) indicators for (macro)economic literacy, that is, objective and subjective knowledge about variables and institutions relevant for macroeconomic policy.
Keywords: E52; E58; E62; H31; Z18; 330; Household survey; New Zealand; Fiscal policy; Public debt; Monetary policy; Public preferences; Economic literacy